The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/aap.0b013e318244179a
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications After Chlorhexidine Antisepsis for Spinal Anesthesia

Abstract: The incidence of neurologic complications possibly associated with spinal anesthesia (0.04%) after CHG skin antisepsis is consistent with previous reports of neurologic complications after spinal anesthesia. These results support the hypothesis that CHG can be used for skin antisepsis before spinal placement without increasing the risk of neurologic complications attributed to the spinal anesthetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…In the face of this, the use of a 2% solution, containing four times the effective concentration of chlorhexidine, seems like unnecessary 'overkill'. Partially in defence of the higher concentration, Checketts cites a large retrospective study of 12 000 neuraxial blocks carried out after skin preparation with chlorhexidine 2%, with no apparent cases of chemicallyinduced arachnoiditis [15]. However, this result would be compatible at the 95% confidence level with an incidence of chlohexidine-related arachnoiditis as high as 1 in 4000 [16].…”
mentioning
confidence: 65%
“…In the face of this, the use of a 2% solution, containing four times the effective concentration of chlorhexidine, seems like unnecessary 'overkill'. Partially in defence of the higher concentration, Checketts cites a large retrospective study of 12 000 neuraxial blocks carried out after skin preparation with chlorhexidine 2%, with no apparent cases of chemicallyinduced arachnoiditis [15]. However, this result would be compatible at the 95% confidence level with an incidence of chlohexidine-related arachnoiditis as high as 1 in 4000 [16].…”
mentioning
confidence: 65%
“…7,52 Preadmission whole-body cleansing and perioperative skin prepping with 2% or 4% CHG has been documented to be a safe and effective risk reduction strategy for preventing surgical site infection. 1,3,4,[21][22][23][24][26][27][28][29][30] Selected animal models have documented meningeal toxicity following direct application of CHG into neural tissues. 53 In actual clinical practice however, when CHG is allowed to thoroughly dry, it been shown to be a safe, efficacious skin disinfectant and can be used for epidural access and cranial or spinal neurosurgical procedures.…”
Section: Intraoperative Irrigation: Does Chg Have a Role In Reducing mentioning
confidence: 99%
“…Conversely, a retrospective cohort study of more than 12,000 patients reported no increased risk in neuraxial complications with the use of chlorhexidine as the skin disinfectant. 60 Furthermore, an in vitro study found chlorhexidine at clinically used concentrations no more cytotoxic that povidone-iodine and calculated that, if allowed to dry, any residual chlorhexidine carried by the block needle tip from skin to subarachnoid space would be diluted 1:145,000. 133 Based on the superiority of chlorhexidine as an antiseptic agent, the advisory panel stands with other national organizations in recommending it as the skin disinfectant of choice before neuraxial procedures.…”
Section: Arachnoiditismentioning
confidence: 99%